Fixed-dose combination of zofenopril plus hydrochlorothiazide vs. irbesartan plus hydrochlorothiazide in hypertensive patients with established metabolic syndrome uncontrolled by previous monotherapy. The ZAMES study (Zofenopril in Advanced MEtabolic Syndrome). Issue 11 (November 2016) - Napoli, Claudio; Omboni, Stefano; Borghi, Claudio
Abstract : Objective: Whether all antihypertensive drugs are equally effective in patients with metabolic syndrome is still unclear. The goal of the Zofenopril in Advanced MEtabolic Syndrome (ZAMES) study was to investigate whether treatment with the fixed-dose combination of sulphydril-containing angiotensin-converting enzyme inhibitor zofenopril plus hydrochlorothiazide is at least as effective as that with the angiotensin receptor blocker irbesartan plus hydrochlorothiazide in patients with metabolic syndrome and essential hypertension, uncontrolled by a previous monotherapy. Methods: We enrolled 721 patients in a multicenter, international (Italy and Romania), randomized, double-blind, parallel group, phase III study. Following a 1-week screening withdrawal period, 482 patients (mean age 59 ± 10 years, 53% men) bearing a SBP at least 140 mmHg and/or DBP at least 90 mmHg plus metabolic syndrome (ATP-III criteria) were randomly allocated to a fixed-dose combination of zofenopril 30 mg plus hydrochlorothiazide 12.5 mg or irbesartan 150 mg plus hydrochlorothiazide 12.5 mg once daily for a cumulative period of 24 weeks. After 8 and 16 weeks, zofenopril and irbesartan doses were doubled in nonnormalized study participants. The study endpoint was the office DBP reduction at study end. In 20% of patients, an ambulatory blood pressure monitoring was performed. Results: The prevalence of diabetes at baseline was significantly ( P  < 0.05) greater in the zofenopril plus hydrochlorothiazide group (82%) than in the irbesartan plus hydrochlorothiazide (73%) group. Baseline-adjusted DBP reductions were superimposable ( P  = 0.370) with zofenopril plus hydrochlorothiazide [ n  = 231; 9.8 (95% confidence interval: 11.1, 8.4) mmHg] and irbesartan plus hydrochlorothiazide [ n  = 235; 10.4 (11.8, 9.0) mmHg]. The same was for SBP [17.0 (19.2, 14.8) mmHg zofenopril plus hydrochlorothiazide vs. 18.8 (21.0, 16.6) mmHg irbesartan plus hydrochlorothiazide, P  = 0.113]. Rate of normalized and responder patients (SBP/DBP < 140/90 mmHg or SBP reduction more than 20 mmHg or DBP reduction more than 10 mmHg) did not differ at study end (65.8% and 77.5% zofenopril plus hydrochlorothiazide vs. 67.7% and 81.5% irbesartan plus hydrochlorothiazide; P  = 0.695, P  = 0.301). These results were confirmed in the 69 study participants undergoing ambulatory blood pressure monitoring (35 zofenopril plus hydrochlorothiazide; 34 irbesartan plus hydrochlorothiazide), with a comparable 24-h average BP reduction [BP difference between-treatment: SBP: 0.1 (−5.7, 5.9) mmHg, P  = 0.975; DBP: −0.9 (−3.8, 2.0) mmHg, P  = 0.541]. Both drugs attained similar BP reductions also in the last 6 h of the dosing interval [between-treatment difference SBP: 0.1 (−7.4, 7.5) mmHg P  = 0.990; DBP: −0.9 (−4.4, 2.6) mmHg, P  = 0.602]. Metabolic and renal indexes were not altered. Few patients were withdrawn for moderate adverse events (5% zofenopril plus hydrochlorothiazide; 5% irbesartan plus hydrochlorothiazide). Conclusion: This is the first study supporting the comparable antihypertensive and metabolic response to fixed-dose combinations of sulphydril-containing angiotensin-converting enzyme inhibitors (zofenopril) or angiotensin receptor blockers (Irbesartan) with a diuretic in patients with advanced metabolic syndrome and nonresponders to monotherapy. The results of this study can further improve the clinical management of high cardiovascular risk patients with hypertension and metabolic syndrome, because these two drug combinations increase the number of available combinations, which may significantly improve patients' adherence in this special clinical condition that is frequently found in everyday practice.